Does Learning Motivation Affect Students’ Achievement in Economics? : Identifying The Internal Factor - Sriyono, Heru; Marfu'i, Lucky Nindi Riandika (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study aims to identify the relationship between learning motivation towards Economics learning achievement of high school students in Bogor Regency, West Java. This research used a quantitative approach. The subject of the study were class XI students of Bogor Regency State High School. The data analysis technique used was inferential statistics using the SPSS 23.0. This correlation study produces data: (1) there are positive and significant relationship between learning motivation and Economics learning achievement, (2) learning motivation of high school students throughout Bogor Regency influences Economics learning achievement, and (3) the increasing motivation of high school students in Bogor Regency will also increase the achievement of learning Economics as well. This study proves that dominantly learning motivation influences Economics learning achievement of high school students in Bogor Regency with a percentage of 70.8%. The results of this study can be followed up by providing guidance and counseling services with the aim of increasing the learning motivation of students who have low motivation to learn.